2008
DOI: 10.1093/tropej/fmn108
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour Problems in Young Children in Rural Bangladesh

Abstract: The prevalence and nature of reported behaviour impairments in rural Bangladesh have implications for public health planning and delivery of health services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 18 publications
0
18
1
2
Order By: Relevance
“…Existing WASH interventions showed to hinder fecal-oral transmission of pathogens, which is responsible for causing undernutrition among children [29]. Common WASH interventions in Bangladesh failed to provide improved environmental hygiene for children as the interventions were not effective to moderate risky behaviors such as crawling and picking objects from contaminated soil and surfaces [29] and pica [40]. …”
Section: Introductionmentioning
confidence: 99%
“…Existing WASH interventions showed to hinder fecal-oral transmission of pathogens, which is responsible for causing undernutrition among children [29]. Common WASH interventions in Bangladesh failed to provide improved environmental hygiene for children as the interventions were not effective to moderate risky behaviors such as crawling and picking objects from contaminated soil and surfaces [29] and pica [40]. …”
Section: Introductionmentioning
confidence: 99%
“…Mullick & Goodman used Development and Well- Being Assessment (DAWBA) questionnaire, and previously validated Strengths and Difficulties Questionnaire (SDQ) tools [22] in their study and found overall prevalence of 15.2% in different settings (rural, urban and urban slum) with the highest prevalence in the urban slum (19.5%) [23]. Another study found 14.6% children with behavioral problems as reported by the parents in rural Bangladesh [24]. Another more recent community-based study reported prevalence of mental disorder among 18.4% of the children [11].…”
Section: Resultsmentioning
confidence: 99%
“…Research in socially disadvantaged and underprivileged groups is also needed to improve the diagnosis, treatment and outcomes in those vulnerable groups [21]. Childhood psychiatric disorders were significantly associated with malnutrition [24], rural residence, low education of fathers, and positive family history [11] which all need a multi-sectorial approach to address these neglected areas. The children mental health survey [11] results provided a baseline measure and resources which can be a basis for taking initiatives for further prevalence study as well as creating provision for effective service delivery models.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 1410 households surveyed, a total of 1496 children in this age group were listed. A systematic sample consisting of every third child listed was pre-selected for developmental screening [4]. In terms of demographic characteristics, the systematic sample was representative of the overall population of children surveyed.…”
Section: Sample Size and Sampling Methodsmentioning
confidence: 99%